Schoolbags and back pain in children between 8 and 13 years: a national study. Issue 2 (May 2017) - Spiteri, Karl; Busuttil, Maria-Louisa; Aquilina, Samuel; Gauci, Dorothy; Camilleri, Erin; Grech, Victor
Schoolbag weight in schoolchildren is a recurrent and contentious issue within the educational and health sphere. Excessive schoolbag weight can lead to back pain in children, which increases the risk of chronic back pain in adulthood. There is limited research regarding this among the Maltese paediatric population. A cross-sectional study was undertaken across all schools in Malta among students aged 8–13 years (inclusive). Data were collected using a questionnaire detailing schoolbag characteristics, self-reported pain and demographic variables, such as age and gender. Structured interviews with participants were also carried out by physiotherapists. A total of 4005 participants were included in the study, with 20% of the total Malta schoolchildren population. Over 70% of the subjects had a schoolbag that exceeded the recommended 10% bag weight to body ratio. A total of 32% of the sample complained of back pain, with 74% of these defining it as low in intensity on the face pain scale–revised. The presence of back pain was statistically related to gender, body mass index (BMI), school and bag weight to body weight ratio. After adjusting for other factors, self-reported back pain in schoolchildren is independently linked to carrying heavy schoolbags. This link should be addressed to decrease the occurrence of back pain in this age group.